Beyond the Breakthrough: The Role of kōan in Post-Awakening Cultivation - Lai, Zhenguo; Shakya, Milan Ratna (Prajñā Journal of Buddhist Studies, 2026)
The Chan (Zen) gong'an (gong'an 公案; Jpn. kōan) has been understood in literature and practice as a didactic device for inducing primary awakening or jianxing (見性; Jpn. kenshō) (Heine 121-40). However, this view overlooks the full scope and sophistication of the kōan system. While breakthrough is central, it occurs within "post-awakening cultivation" (wuhou baoren, 悟 後 保 任 ) . Employing textual-historical and doctrinal analysis, this study traces Guifeng Zongmi's (圭峰宗密) "sudden enlightenment, gradual cultivation" theory, contextualizes Dahui Zonggao's (大慧宗杲) Kanhua Chan (看話禪, "observing the phrase" Chan) in the Song dynasty, and analyzes Linji/Rinzai pedagogical techniques including verificatory kōans (kanyan, 勘驗), "checking questions" (Jpn. sasshō, 拶所), and "capping phrases" ( Jpn. jakugō, 着 語 ) to establish the kōan as essential for verifying awakening authenticity, deepening insight, refining karmic habits, and integrating enlightenment into daily life. This fills gaps in post-awakening Chan (Zen) knowledge, reframing the kōan as a comprehensive pathway from "sudden enlightenment" to perfected cultivation and Buddhahood. The paper's original contribution is reconceptualizing the kōan beyond a mere breakthrough trigger into a lifelong soteriological system, bridging doctrinal foundations with practical pedagogy in contemporary Chan (Zen) studies.